Perianal Pediatric Crohn Disease Is Associated With a Distinct Phenotype and Greater Inflammatory Burden. Issue 3 (September 2017) - Assa, Amit; Amitai, Michal; Greer, Mary-Louise; Castro, Denise A.; Kuint, Ruth C.; Martínez-León, Maria; Herman-Sucharska, Izabela; Coppenrath, Eva; Anupindi, Sudha; Towbin, Alexander; Moote, Douglas; Konen, Osnat; et al.
ABSTRACT: Objectives: Data on the outcomes of children with perianal Crohn disease (pCD) are limited, although its presence is often used for justifying early use of biologics. We aimed to assess whether pCD in children is associated with more severe outcomes as found in adults. Methods: Data were extracted from the ImageKids database, a prospective, multicenter, longitudinal cohort study. The study enrolled 246 children at disease onset or thereafter. All patients underwent comprehensive clinical, endoscopic, and radiologic evaluation at enrollment; 98 children had repeat evaluation at 18 months. Results: Of the 234 included patients (mean age 14.2 ± 2.4 years; 131 [56%] boys), 57 (24%) had perianal findings, whereas only 21 (9%) had fistulizing perianal disease. Children with pCD had reduced weight and height z scores compared with non-pCD patients (−0.9 vs −0.35, P = 0.03 and −0.68 vs −0.23, respectively; P = 0.04), higher weighted pediatric CD activity index (32 [interquartile range 16–50] vs 20 [8–37]; P = 0.004), lower serum albumin (3.6 ± 0.7 vs 4.5 ± 0.8, P = 0.016), and higher magnetic resonance enterography global inflammatory score ( P = 0.04). Children with pCD had more rectal (57% vs 38%, P = 0.04), and jejunal involvement (31% vs 11% P = 0.003) and a higher prevalence of granulomas (64% vs 23%, P = 0.0001). Magnetic resonance enterography–based damage scores did not differ between groups. Patients with skin tags/fissures only, had similar clinical, endoscopic, and radiologic characteristics as patients with no perianal findings. Conclusions: Pediatric patients with pCD with fistulizing disease have distinct phenotypic features and a predisposition to a greater inflammatory burden. Abstract : Supplemental Digital Content is available in the text